Pengaruh Model Pembelajaran Problem Based Learning Berbantu Media Kantong Perkalian Terhadap Pemahaman Konsep Matematika Kelas II MI Islamiyah Sumberwudi - Maqoosidhan Nadhiifah; Lailatul Maghfiroh (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2026)
This research is motivated by the fact that many students have difficulty understanding mathematical concepts, especially in multiplication. One alternative is to use the Problem Based Learning model assisted by multiplication bag media to help students understand the concept of multiplication through real problems assisted by the use of concrete and interesting media. The researcher aims to determine the effect of the Problem Based Learning model assisted by multiplication bag media on the understanding of mathematical concepts in multiplication material for class II students of MI Islamiyah Sumberwudi. This study uses quantitative research with a quasi-experimental method with pre-test and post-test with non-equivalent control-group design. The sample used was 40 students, consisting of two classes, namely class II A as the experimental class and class II B as the control class. Data collection techniques used were observation, tests, and documentation. Data analysis used was descriptive statistics, inferential analysis including normality tests, homogeneity tests, and hypothesis testing with independent t-tests. The results showed that the average posttest score of the experimental class was 80.6 and the average score of the control class was 67.75, which means that the experimental class score was higher than the control class. Based on the results of the hypothesis test with the Independent sample t-test, the Sig (2-tailed) value was 0.005 < 0.05 and the calculated t value > t table (3.013 > 2.024), which means that H0 is rejected and H1 is accepted.